1998
DOI: 10.1086/306351
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Abundances in Unevolved Metal‐poor Stars from Near‐Ultraviolet OH Lines

Abstract: of unevolved stars, when compared with values in the literature for giants of similar metallicity, imply that the latter may have su †ered a process of oxygen depletion. As a result, unevolved metal-poor stars shall be considered better tracers of the early evolution of oxygen in the Galaxy. The higher [O/Fe] ratios we Ðnd in dwarfs has an impact on the age determination of globular clusters, suggesting that current age estimates have to be reduced by about 1È2 Gyr.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
289
7

Year Published

1999
1999
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(344 citation statements)
references
References 49 publications
(97 reference statements)
48
289
7
Order By: Relevance
“…On the other hand, both the CRS and LECR models predict a linear evolution, consistent with the observations, although Fields & Olive (1998) recently suggested that the CRI model should still be considered as viable, based on their re-analysis of the data including O in low metallicity stars (Israelian, Garcia Lopez, & Rebolo 1998).…”
Section: Introduction and Overviewsupporting
confidence: 64%
See 1 more Smart Citation
“…On the other hand, both the CRS and LECR models predict a linear evolution, consistent with the observations, although Fields & Olive (1998) recently suggested that the CRI model should still be considered as viable, based on their re-analysis of the data including O in low metallicity stars (Israelian, Garcia Lopez, & Rebolo 1998).…”
Section: Introduction and Overviewsupporting
confidence: 64%
“…For both the CRS and LECR cases, the accelerated particle composition is independent of [Fe/H] and the same as that of the current epoch cosmic rays, except that there are no protons and α-particles for the latter. The ambient medium composition is solar scaled with Fe/H, except that for the CRI case we also consider a slower decrease of the O abundance, O/H=(O/H) 10 0.6 [Fe/H] , which fits the recent Israelian et al (1998) data. Such a modification of the ambient medium abundances has only a negligible effect on the calculations for the CRS and LECR models.…”
Section: The Energetics Of Be Productionmentioning
confidence: 75%
“…In order to convert from [O/H] to the iron metallicities [Fe/H], we have used the extensive sample of disk stars by Edvardsson et al (1993), from which we derive the relationship The dashed line is the predicted relationship on the basis of the radial gradients of young objects in the galactic disk, at galactocentric distances 4 ≤ R(kpc) ≤ 12, as discussed by Maciel (2002). The figure also includes some representative observational data by Barbuy & Erdelyi-Mendes (1989), asterisks; Boesgaard et al (1999), filled squares; Edvardsson et al (1993), crosses;Israelian et al (1998), solid dots; Spiesman & Wallerstein (1991), open circles; Spite & Spite (1991), plus signs; Takeda et al (2002), empty squares; Mishenina et al (2000), open stars, and Cavallo et al (1997), filled stars, as recomputed by Mishenina et al (2000).…”
Section: The [O/h] × [Fe/h] Relationmentioning
confidence: 76%
“…Attention was sharply focussed on oxygen abundances in metal-poor stars by studies of the OH ultraviolet lines (Israelian et al 1998(Israelian et al , 2001Boesgaard et al 1999). These showed that [O/Fe] …”
Section: [O I] and The Oxygen Problemmentioning
confidence: 99%
“…A comparison is illuminating given the heat the "oxygen problem" has generated in recent times. Eight of our programme stars were analysed by Israelian et al (1998) or Israelian et al (2001). Differences in adopted model atmosphere parameters are small: ∆T eff = 91 ± 103 K, ∆ log g = 0.18 ± 0.26, and ∆ [Fe/H] (Table 4) and those from OH is −0.06 dex.…”
Section: [O I] and Oh Linesmentioning
confidence: 99%